Taqiyyah sebagai Peneguhan Harmoni dan Toleransi: Studi Aksiologi - Ulya, Ulya (FIKRAH, 2021)
Every behavior cannot be freely valued, including religious behavior which has been carried out by the Shia community. This article examines the values inherent in the taqiyya carried out by the Shia community in Banjaran Village, Bangsri, Jepara Regency. The problems which are answered: how the concept of Taqiyya according to Shia community in Banjaran; how they practice it in socio-religious life; and what values are put forward from the implementation of taqiyya. Answering these problems based on a descriptive qualitative research. Data was collected from Shia figures, Shia believers, village chief and secretaries, as well as non-Shia residents. Data collection is carried out through non-participatory observation, semi-structured interviews, and documentation. Triangulation technique is used to check the credibility of the data. The analysis technique uses the interactive analysis model of Miles and Huberman. The results of the study indicate that taqiyya according to the Shia community in Banjaran is to refrain from revealing their Shia identity. They implement it, both in matters of worship and social interaction, when they are forced. Taqiyya is carried out by the Shia community in Banjaran within the framework of its function as an expression of obedience, as well as a strategy of self-defense and belief, as well as a strategy to adapt thus its existence is accepted and does not disturb society in general. This is where in the practice of taqiyya religious and social values are attached. These values contribute to the strengthening of harmony and tolerance in Banjaran.